Alcohol reduction in the first trimester is unrelated to smoking, patient or pregnancy characteristics. (June 2017) - Schmidt, Kristen A.; Lancia, Andrew J.; Alvi, Saad; Aldag, Jean C.
Abstract: Introduction: Studies show alcohol-preferring mice reduce their alcohol intake during pregnancy; this study questions if the same is true for humans. The current investigation compares women's pre-pregnancy and first trimester alcohol consumption, examines if women with problem drinking diminish their alcohol intake during pregnancy, and determines if prenatal alcohol reduction is associated with characteristics of pregnancy, patients or smoking. Methods: 126 participants in weeks 1–12 of pregnancy, recruited from Obstetric and Family Practices, completed a survey during their initial prenatal visit including two gender-specific AUDITs (Alcohol Use Disorders Identification Tests) querying current and pre-pregnancy alcohol use. AUDIT-C (AUDIT items 1–3) scores measuring pre-pregnancy and first trimester alcohol consumption were compared, analyzed and tested using general linear model repeated. A p ≤ 0.05 was accepted as significant. Results: Most participants were multiparous, Caucasian high school graduates experiencing nausea and vomiting. Pre-pregnancy alcohol use was significantly (p = 0.019, Fisher's exact) higher among women seeing obstetricians. Pre-pregnancy AUDIT-C scores (m (mean) = 2.22, sd (standard deviation) = 2.19) were significantly higher (p < 0.001) than first trimester scores (m = 0.143, sd = 0.532). Among 49 with pre-pregnancy AUDIT-C scores ≥ 3, 45/49 (92%) reduced their alcohol use to zero during the first trimester. Age, race, education, marital status, parity, nausea and vomiting, gestational age and smoking were non-factors in score reduction. Conclusions: Women reported reducing their alcohol consumption during pregnancy, including those screening positive for pre-pregnancy problem drinking. First trimester alcohol reduction cannot be accounted for by smoking, patient or pregnancy characteristics; public health initiatives, psychological factors and hormonal mechanisms may be implicated. Highlights: Pre-pregnancy problem drinking is more common in patients seeking specialty care. Problem drinking is significantly reduced during pregnancy's first trimester. There was no association between pregnancy or patient characteristics and reduced alcohol consumption during pregnancy. Smoking status was not associated with alcohol use reduction in pregnant females.